THE WALLS Of ByZANTIUM : THE MISTRA CHRONICLES - Heneage, James (London, : Heron Books, 2013)
This sweeping historical novel is shaped by the quest for a mysterious relic, guarded through generations, and by one man that might yet save the threatened Byzantine empire. In an age of clashing empires, dark forces from the east are endangering the first light of the western Renaissance. It is an age of ruthless rulers, divided churches, fractured dynasties and intrepid traders. It is an age of great cities like Venice and Constantinople; an age of conquerors like Tamerlane who will drown the world in blood; an age when only a hero of exceptional gifts can make a difference. Luke Magoris is that hero. Born the son of one of the Varangian guards who had sworn to keep the secret relic safe, he will find himself committed to a long journey to discover ? and try to avoid ? his destiny. He will travel from battle to trading fortune, from horse dealing to captivity, and to the love of three very different women and the unrelenting enmity of two remarkable men.